PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA KACER TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA - Khoiruzzad, Asif; Erna Zumrotun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The importance of critical thinking in education cannot be overstated. Yet, students often demonstrate minimal involvement in their learning journey, showing a tendency to remain passive. Hence, this study aimed to explore how Problem-Based Learning (PBL) aided by the 'kacer' (white-rumped shama) media affects students' critical thinking skills. Employing a pre-experimental design method, specifically the "one group pretest-posttest design," allowed for the observation of changes in critical thinking abilities before and after implementing the PBL approach with 'kacer' media support. The study involved 15 fourth-grade students from SD N 02 Kuanyar. Results revealed a notable enhancement in critical thinking skills post PBL with 'kacer' media integration. Thus, it can be inferred that utilizing the PBL method alongside 'kacer' media positively impacts students' critical thinking capabilities, advocating for its incorporation in future educational methodologies.